2019
DOI: 10.1186/s13063-019-3595-x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of polyglycolic acid felt reinforcement in preventing postoperative pancreatic fistula after pancreaticojejunostomy in patients with main pancreatic duct less than 3 mm in diameter and soft pancreas undergoing pancreatoduodenectomy (PLANET-PJ trial): study protocol for a multicentre randomized phase III trial in Japan and Korea

Abstract: Background Partial pancreatoduodenectomy is performed for malignant and benign diseases of the pancreatic head region. The procedure is considered highly difficult and highly invasive. Postoperative pancreatic fistula (POPF) is an important complication because of several consequent complications, including intraabdominal haemorrhage, often increasing hospital stays and surgical mortality. Although many kinds of pancreaticojejunostomy aimed at reducing POPF have been examined to date, the techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…A polyglycolic acid mesh sheet is a tissue-strengthening agent that reduces air or fluid leakage from the surgical site. Many clinical studies have been conducted, and they proved the preventive effect of polyglycolic acid mesh sheets for air, fluid and bowel content leakage [ 9 , 11 , 12 , 13 , 14 , 15 , 16 , 18 ]. However, no study has shown that the polyglycolic acid mesh sheet is effective in thyroid surgery for reducing exudate or chyle leakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A polyglycolic acid mesh sheet is a tissue-strengthening agent that reduces air or fluid leakage from the surgical site. Many clinical studies have been conducted, and they proved the preventive effect of polyglycolic acid mesh sheets for air, fluid and bowel content leakage [ 9 , 11 , 12 , 13 , 14 , 15 , 16 , 18 ]. However, no study has shown that the polyglycolic acid mesh sheet is effective in thyroid surgery for reducing exudate or chyle leakage.…”
Section: Discussionmentioning
confidence: 99%
“…A polyglycolic acid mesh sheet (Neoveil™) is a tissue-strengthening repair agent that prevents air or fluid leakage after surgery. The preventive effect of polyglycolic acid mesh sheets has been proven in various surgical fields; these sheets diminish air leakage after lung resection surgery [ 9 , 10 , 11 , 12 ], reduce the pancreatic fistula incidence in pancreas resection [ 13 , 14 , 15 , 16 ], prevent bile leakage and hemorrhage after liver resection [ 17 ], and prevent bowel content leakage after colon surgery [ 18 ]. However, there are no clinical studies on whether polyglycolic acid mesh sheets can reduce exudates from the neck node dissection area and have a protective effect against chyle in thyroid surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Various modifications of surgical techniques have been applied according to surgeons’ preferences, including the Blumgart method [ 5 7 8 9 10 11 13 14 16 18 20 ]. Although none of them have been found to be superior to another, new attempts to reduce POPF are still ongoing, such as applying polyglycolic acid or fibrinogen/thrombin-coated collagen patch [ 1 2 3 12 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been attempts to reduce the occurrence of POPF by applying various techniques, but the results are still controversial [ 2 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 ]. Pancreaticojejunostomy (PJ), which anastomoses the pancreatic stump to the jejunal loop, was popularized by Whipple in the 1940s [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative pancreatic fistula (POPF) is the most common and intractable complication after partial pancreatectomy, with an incidence of 13% to 64%. [ 1 4 ] Although the development of surgical techniques and lots of new experimental attempts in perioperative management has significantly reduced the mortality of pancreatic surgery, [ 5 ] the postoperative complications are still high, reaching 40% to 50%. [ 6 ] Leakage of pancreaticojejunostomy or POPF is the major complication after a pancreatectomy.…”
Section: Introductionmentioning
confidence: 99%